Clenbuterol residue in beef meat collected from several cities in Java Island, Indonesia - Raphaella Widiastuti; Yessy Anastasia (Jurnal Ilmu Ternak dan Veteriner, 2018)
Clenbuterol (CLB) (see Figure 1) is an illegally animal drug of the β-agonist group that used as a promoter of growth in various farm animals. The presence of CLB residues in livestock products can cause poisoning in humans such as tremor, tachycardia, nausea and dizziness. The purpose of this research is to develop CLB residue detection method on beef detected using high performance liquid chromatography (HPLC) and to know the presence of CLB residue on 74 samples of frozen and fresh meat from several cities in Java. Samples were extracted with acetonitrile and isopropanol, then analyzed chromatographically using RDS ODS C18 column and mixed mobile phases of 50 mM NaH2PO4 and acetonitrile (80:20, v/v) and detected by photodiode array detector at 210 nm wavelength. The recoveries test at spiked concentrations of 2, 5 and 10 ng/g were 103.45, 89.27 and 89.53% for each additional concentrations. The detection limit and the quantitation limit were 0.10 ng/g and 0.31 ng/g, respectively. Analysis of 74 samples showed that CLB residue was detected in 8 samples in a concentration range of 2.40 to 15.06 ng/g and had exceeded the CLB residue maximum limit of 0.2 ng/g. To avoid the risk of the presence of CLB residues, it is necessary to regularly monitor the residue content of livestock food to ensure food safety for consumers.